On Nonlinear Dynamics and an Optimal Control Design to a Longitudinal Flight - Pereira, Danilo Carlos; Balthazar, José Manoel [UNESP]; Chavarette, Fábio Roberto; Rafikov, Marat (Asme-amer Soc Mechanical Eng, 2008)
In this work, we analyzed a bifurcational behavior of a longitudinal flight nonlinear dynamics, taking as an example the F-8 aircraft Crusader. We deal with an analysis of high angles of attack in order to stabilize the oscillations; those were close to the critical angle of the aircraft, in the flight conditions, established. We proposed a linear optimal control design applied to the considered nonlinear aircraft model below angle of stall, taking into account regions of Hopf and saddled noddle bifurcations.
Keywords: F-8 aircraft Crusader; bifurcations; optimal linear control design